Common ECG Lead Placement Errors. Part II: Precordial Misplacements - Allison V. Rosen; Sahil Koppikar; Catherine Shaw; Adrian Baranchuk (University Library System, University of Pittsburgh, 2014)
Background: Electrocardiography is a very useful diagnostic tool. However, errors in placement of ECG leads can create artifacts, mimic pathologies, and hinder proper ECG interpretation. This is the second of a two-part series discussing how to recognize and avoid these errors. Methods: 12-lead ECGs were recorded in a single male healthy subject in his mid 20s. Various precordial lead misplacements were compared to ECG recordings from correct lead placement. Results: Precordial misplacements caused classical changes in ECG patterns. Techniques of differentiating these ECG patterns from true pathological findings were described. Conclusion: As in Part I of this series, recognition and interpretation of common ECG placement errors is critical in providing optimal patient care.